The Cheat Book - Ramzee, ....-; CZap, K., ....- (London : Hodder & Stoughton, 2024)
Forgotten your homework and need to wing it? Wish you could talk your way out of detention? Want to squash your bullies and rise to the top? Join Kamal as he attempts to go from puke boy to popular! Kamal is better than anyone else in his school at fading into the background. When you're a refugee and you've started a new school three times in as many years, you learn to keep your head down. But, after a major puke incident in front of the whole school, being invisible is no longer an option. And when Kamal finds a mysterious cheat book in the library that promises to help him gain popularity, he sees a chance to finally make his mark. This hilarious guide to being 'too cool for school' (or just cool enough) from brilliant author-illustrator RAMZEE has black-and-white illustrations throughout and is perfect for 8+ readers.
Keywords: Engels; Graphic novels; Secundair onderwijs; Stripverhaal; To cheat